Influence of Problem Based Learning Modelsand Gender to Ability Student Mathematic Communication - Muhammad Ardian; Asmin Asmin; Zul Amry (BIRCU, 2020)
This study aims to determine how the effect of problem-based learning models and gender on students' mathematical communication skills. By using data sources, namely primary data sources and secondary data, the primary data sources in this study were data that contained the research title, and secondary data in this study were supporting books related to the research title. The method used is the literature study. The results of this study indicate that the problem-based learning model has an influence on mathematical communication because each step in learning can support the development of students 'mathematical communication skills, the gender-based learning model has an influence on students' mathematical communication skills , but between female and male students different abilities.